Properties of concrete with eggshell powder and tyre rubber crumb - Chong, Beng Wei; Rokiah, Othman; Putra Jaya, Ramadhansyah; Doh, Shu Ing; Li, Xiaofeng; Noram Irwan, Ramli (Trans Tech Publications, Switzerland, 2021)
Solid waste management is one the leading problems in Malaysia. Rapid development and population growth have prompted researches to improve the recycling and reusing of waste material for sustainable development. Chicken eggshell is discarded in Malaysia as municipal waste, while waste tyre is a waste that is difficult to handle and often ends up in the landfill. This paper presents the properties of high performance concrete with eggshell powder and tyre rubber crumb as partial replacement of cement and sand. Grade 45 concrete was prepared with 5% tyre rubber crumb as sand replacement and up to 15% of eggshell powder as cement replacement. The mechanical strength of concrete was investigated for up to 90 days while durability properties were studied through water absorption and carbonation test. Results show that concrete with 5% eggshell powder is optimal for high mechanical properties, lower water absorption and low carbonation depth. X-Ray Diffraction of concrete shows increase of calcite compound which contributes to the gain of strength. Microstructure analysis with SEM and EDX provides insight of the improved performance, which is attributed to a denser C-H-S gels and finer pore structure.